2013
DOI: 10.4103/0970-0358.113714
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil significantly reduces ischemia reperfusion injury in skin island flaps

Abstract: Introduction:Numerous pharmacological agents have been used to enhance the viability of flaps. Ischemia reperfusion (I/R) injury is an unwanted, sometimes devastating complication in reconstructive microsurgery. Tadalafil, a specific inhibitor of phosphodiesterase type 5 is mainly used for erectile dysfunction, and acts on vascular smooth muscles, platelets and leukocytes. Herein, the protective and therapeutical effect of tadalafil in I/R injury in rat skin flap model is evaluated.Materials and Methods:Sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…PDE5 inhibitors have been shown to potentiate the vasodilator effect of NO, improving vascular function in patients with erectile dysfunction, pulmonary arterial hypertension, portal hypertension, and in cirrhotic rat liver [17,19–21]. Furthermore, it has been shown that the administration of TDF may also be useful against ischemic injury in other organs and tissues such as neurons, skin island flaps, ovary, myocardium, and kidney [10,22–25]. Baek et al.…”
Section: Discussionmentioning
confidence: 99%
“…PDE5 inhibitors have been shown to potentiate the vasodilator effect of NO, improving vascular function in patients with erectile dysfunction, pulmonary arterial hypertension, portal hypertension, and in cirrhotic rat liver [17,19–21]. Furthermore, it has been shown that the administration of TDF may also be useful against ischemic injury in other organs and tissues such as neurons, skin island flaps, ovary, myocardium, and kidney [10,22–25]. Baek et al.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase specifically inhibits the nitric oxide in the pathway of smooth muscle vessel. Tadalafil, by loosening the smooth muscles, increases the local perfusion and dilation of the vessels and inhibits platelet aggregation (Kayiran, Cuzdan, Uysal, & Kocer, ; Kulkarni & Patil, ), and also some study shows that the tadalafil has positive effect in the prevention of I/R injury(Kayiran et al., ; Kulkarni & Patil, ). Verapamil is a calcium channel blocker drug that derivates from phenylalkylamine and approved by FDA (Sertkaya et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The lengthewidth ratio cannot be >2:1, greatly limiting therapy applications of random skin flaps. Previous studies [3,4] have confirmed that ischemiaereperfusion (I/R) injury and neutrophil infiltration result in flap necrosis. Various kinds of agents have been tested to prevent skin flap ischemia, such as resveratrol [5], heparin [6], and vascular endothelial growth factor (VEGF) [7].…”
Section: Introductionmentioning
confidence: 83%